Electrochemical biosensors for pathogen detection - Cesewski, Ellen; Johnson, Blake N. (Biosensors & bioelectronics, 2020)
Recent advances in electrochemical biosensors for pathogen detection are reviewed. Electrochemical biosensors for pathogen detection are broadly reviewed in terms of transduction elements, biorecognition elements, electrochemical techniques, and biosensor performance. Transduction elements are discussed in terms of electrode material and form factor. Biorecognition elements for pathogen detection, including antibodies, aptamers, and imprinted polymers, are discussed in terms of availability, production, and immobilization approach. Emerging areas of electrochemical biosensor design are reviewed, including electrode modification and transducer integration. Measurement formats for pathogen detection are classified in terms of sample preparation and secondary binding steps. Applications of electrochemical biosensors for the detection of pathogens in food and water safety, medical diagnostics, environmental monitoring, and bio-threat applications are highlighted. Future directions and challenges of electrochemical biosensors for pathogen detection are discussed, including wearable and conformal biosensors, detection of plant pathogens, multiplexed detection, reusable biosensors for process monitoring applications, and low-cost, disposable biosensors. •Comprehensive review of electrochemical biosensor-based pathogen detection.•Review of emerging electrodes for transduction of pathogen binding via electrochemical methods.•Discussion of emerging electrochemical biosensor designs, including flexible and wearable form factors.•Highlight of electrochemical biosensors for coronavirus detection.